Attention, spatial representation, and visual neglect: simulating emergent attention and spatial memory in the selective attention for identification model (SAIM). - Heinke, D; Humphreys, G (2003)
The selective attention for identification model (SAIM) is presented. This uses a spatial window to select visual information for recognition, binding parts to objects and generating translation-invariant recognition. The model provides a qualitative account of both normal and disordered attention. Simulations of normal attention demonstrate 2-object costs and effects of object familiarity on selection, global precedence, spatial cueing, and inhibition of return. When lesioned, SAIM demonstrated either view- or object-centered neglect or spatial extinction, depending on the type and extent of lesion. The model provides a framework to unify (a) object- and space-based theories of normal selection, (b) dissociations within the syndrome of unilateral neglect, and (c) attentional and representational accounts of neglect.